Architectural Heritage Analysis of the Yuanying Guan Pavilion: Construction and Signification - Manuel V. Castilla (Heritage, 2023)
This paper aims to analyse the structural function and symbolic function of the historic building Yuan Guan during the inculturation process in the early Qing dynasty in China. This process was the dominant Western practice during the early Qing dynasty, when technology, design, aesthetics, and linear perspective were considered indispensable tools to express the nature of an architectural encounter between China and Europe. Given the artistic–cultural richness of this context, the masterwork Yuanying Guan complex can be examined from a spatial semiotic study in an original and unique way. Thus, semiotic tools were used to interpret the expression of the architectural space and to formulate a subsequent understanding of the architectural forms of this destroyed heritage, turning each element into a tool of communication.